Business purchasing focused on sustainable development. The role of ISO 20400 standard - Brzeziński, Jakub; Rudnicka-Reichel, Agata (Wybrane aspekty zarządzania procesami, projektami i ryzykiem w przedsiębiorstwach, 2020)
The aim of the paper was to present the issues of sustainable development in the purchasing process. Enterprises are increasingly looking for solutions that will allow them to reconcile business interests with social expectations and changing regulations. The purchasing process is key to achieving business goals. The inclusion of social and environmental issues at the purchasing strategy stage allows to manage challenges comprehensively. Organizations have several ways to integrate sustainable development. One of them is the ISO 20400 guidelines devoted entirely to sustainable purchasing. The document allows to go through priority areas for the process and facilitates the understanding of the essence of social and environmental aspects of purchasing. It presents an approach based on universal international guidelines.